2019
DOI: 10.1007/s40093-019-0261-y
|View full text |Cite
|
Sign up to set email alerts
|

Aerated chicken, cow, and turkey manure extracts differentially affect lettuce and kale yield in hydroponics

Abstract: Purpose Manure extracts possess great potential as alternate inorganic fertilizers. However, limited information exists on how manure influences plant growth. This study's aim was to determine the impact of aerated manure extracts on romaine lettuce (Lactuca sativa var. longifolia) and Russian kale (Brassica napus var. 'Red Russian') in hydroponic systems. Methods Chicken, cow, and turkey manure extract solutions (10, 25, and 50 g/L manure) were compared to a control (Hoagland) solution for lettuce and kale gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…An alternative to these conventional fertilizers is the use of organic fertilizers derived from plant and animal byproducts such as seaweed extract, manure or hydrolyzed fish emulsion [6] which require the development of microbial communities to mineralize complex organic compounds to make them plant available [7,8]. Drawbacks of organic fertilizers include variable, significantly reduced yield [9][10][11] which may be attributed to unstable microbial activity, difficulty supplying the proper proportion of nutrients, high pH as well as the development of biofilm in the organically fertilized hydroponic reservoirs [12]. Regarding biofilm, it is believed that the suspended organic matter which can develop on plant roots can also clog pumps/recirculation lines, reduce oxygen and nutrient uptake by roots and deplete nutrient solution oxygen levels [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…An alternative to these conventional fertilizers is the use of organic fertilizers derived from plant and animal byproducts such as seaweed extract, manure or hydrolyzed fish emulsion [6] which require the development of microbial communities to mineralize complex organic compounds to make them plant available [7,8]. Drawbacks of organic fertilizers include variable, significantly reduced yield [9][10][11] which may be attributed to unstable microbial activity, difficulty supplying the proper proportion of nutrients, high pH as well as the development of biofilm in the organically fertilized hydroponic reservoirs [12]. Regarding biofilm, it is believed that the suspended organic matter which can develop on plant roots can also clog pumps/recirculation lines, reduce oxygen and nutrient uptake by roots and deplete nutrient solution oxygen levels [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…But in contrast, Wortman et al (2016) found that strawberry yield was increased 15% more in synthetic nutrient solution than the bio-based, liquid nutrient source and vermicompost mixed with soilless media. Tikasz et al (2019) reported that Lettuce grown in a compost tea extracted from the animal manures produced higher above ground dry mass compared to the commercialy avialble Hoagland solution, but, the success depnds on the careful monitoring of NO3−, NH4+, Ca, Mg, Mn, and Na. Liquid organic fertilizers produced from waste molasses, distillery slop and sugarcane leaves produced similar growth and yield as synthetic fertilizer solution of Green Cos Lettuce (Lactuca sativa var.…”
Section: Plant Growth Parametersmentioning
confidence: 99%
“…Therefore, bioponics presents several challenges as it involves a living organic environment that conventional hydroponics do not have to deal with. The management of physicochemical parameters such as pH and electroconductivity can differ and be more complex than in conventional hydroponics [32,34]. Furthermore, the major challenge is to provide a satisfactory nutrient solution for plants, containing all the essential nutrients in adequate quantities, and free of phytotoxic substances [2,35].…”
Section: Introductionmentioning
confidence: 99%
“…However, the biochemical processes involved in their manufacturing and the original organic materials from which they are derived are not explicit. Various studies have explored methods of producing nutrient solutions from organic sources and compared them with their efficiency on plants [21,34,40,41]. These studies are of interest, as they show that one can implement bioponics in any context, using local organic waste.…”
Section: Introductionmentioning
confidence: 99%